Effect of Athena SWAN funding incentives on women's research leadership. (26th October 2020) - Ovseiko, Pavel V; Taylor, Mark; Gilligan, Ruth E; Birks, Jacqueline; Elhussein, Leena; Rogers, Mike; Tesanovic, Sonja; Hernandez, Jazmin; Wells, Glenn; Greenhalgh, Trisha; Buchan, Alastair M
Abstract : Analysis shows that funding incentives can work and more funders should trial them, say Pavel V Ovseiko and colleagues